Multiple deprivation and geographic distance to community physical activity events — achieving equitable access to parkrun in England. (December 2020) - Schneider, P.P.; Smith, R.A.; Bullas, A.M.; Quirk, H.; Bayley, T.; Haake, S.J.; Brennan, A.; Goyder, E.
Abstract: Objectives: To evaluate geographic access to free weekly outdoor physical activity events ('parkrun') in England, with a particular focus on deprived communities, and to identify optimal locations for future events to further maximise access. Study design: This study is a cross-sectional ecological analysis of the socio-economic disparities in geographic access to parkrun events in England in late 2018. Methods: We combined geolocation data on all English Lower Layer Super Output Areas and parkrun events to calculate geodesic distances to the nearest event for more than 32, 000 communities in England. We use this measure of geographic access to summarise the relationship between access and socio-economic deprivation, measured using the index of multiple deprivation. We then used geographic coordinates of public green spaces in England to conduct a simple location-allocation analysis to identify 200 locations for future event locations that would maximise access. Results: In England, 69% of the population live within 5 km of one of the 465 parkrun events. There is a small negative correlation between distance and deprivation, indicating that access is slightly better in more socio-economically deprived areas. Setting up an additional 200 events in optimal locations would improve access: the average distance to the nearest parkrun event would improve by 1.22 km, from 4.65 km to 3.43 km, and approximately 82% of the English population would live within 5 km of a parkrun event. Conclusion: Over two-thirds of the English population live within 5 km of a parkrun event, and contrary to our expectation, we find that geographic access is slightly better for those living in more deprived communities. Creating additional events may improve geographic access, but effective strategies will still be needed to increase engagement in new and existing events by those living in socio-economically deprived areas. Highlights: Parkrun in a grass-roots movement that organises free weekly 5 km running and walking events. In England, the median distance to the nearest parkrun event was 3.4 km; 69% of the population lived within 5 km of an event. Access showed no negative socio-economic gradient. In fact, people in deprived communities had better geographic access. Sport England provided funding to set up 200 new events. We identified optimal locations, to further maximise public access.